Economic sizing and placement of hydrogen fueling and electric vehicles charging stations powered by renewable and battery systems in smart distribution network - Mehdi Veisi (Results in Engineering)
This article discusses the planning, sizing, and placement of a vehicle refueling station supplied by renewable energy systems, including photovoltaic, wind, biomass units, and an integrated battery system within a smart distribution network. The proposed station comprises facilities for hydrogen fueling and electric vehicle charging stations, structured as a bi-level optimization approach. The upper-level model focuses on the planning phase of the refueling station. Its objective is to minimize annual costs associated with construction, maintenance, and operation. Key constraints involve operational planning for renewable sources, battery systems, and vehicle refueling stations while accounting for reactive power management. In contrast, the lower-level formulation deals with the eco-scheduling of smart distribution grid. Its goal is to minimize the sum of annual energy losses and operation costs within the grid, governed by linearized optimal power flow model. To account for uncertainties in demand, energy prices, renewable generation output, and refueling station performance, a stochastic optimization framework is employed. The solution is derived using Benders decomposition algorithm to achieve optimal results. The primary innovation highlighted in this paper includes integrating renewable resources and battery systems to power the refueling station, leveraging reactive power control for improved station performance, and addressing both operational and economic objectives in the distribution system. Numerical results underscore the advantages of this strategy. Constructing a refueling station without battery and renewable units leads to significant drawbacks, an increase in network operation cost by 144.6 % and grid energy loss by 167.6 %. Voltage levels drop below 0.9 per-unit, and distribution lines experience severe loading of up to 34.7 %. In contrast, the proposed plan enhances network economics by 51.3 %-74.5 % and operational conditions by 17.7 %-148.1 %, effectively showcasing the benefits of incorporating sustainable technologies and advanced planning methods into refueling station development.